Using Duolingo Application in Teaching Vocabulary at Seventh Grade of SMPN 3 Pitumpanua - Tsamratulaeni (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2023)
This research aims to improve students' vocabulary mastery and to find out that the Duolingo application is effective for improving vocabulary. Based on the researcher's experience by using the Duolingo application in learning vocabulary, wants to find out that whether this application is effective in improving the students' vocabulary, and also in learning especially English learning students never used technological media as a media for learning language English. the subject of this research were seventh grade students of SMPN 3 Pitumpanua Kabupaten Wajo. The method of this research is quantitative method. The researcher used a pre-experimental design. To compare the students’ score setelahdiberikan, after giving a treatment and post-test, there are an increase number of scores of researchers than the pre-test, The data show that student improve their understand and memorize English vocabulary. The result of the analysis showed a significant different, in the pre-test the students' mean score was 61.33 and post-test was 91.00. This is also seen in the results of the probability value is less than α (0.000 <0.05), this indicates that the alternative hypothesis (H1) is accepted, and the null hypothesis (H0) is rejected. Based on the results of the research, it was concluded that the use of Duolingo application is effective to improve vocabulary mastery at seventh grade researcher of SMPN 3 Pitumpanua Kabupaten Wajo